1989
DOI: 10.1099/00221287-135-9-2379
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chlamydia trachomatis Infection on the Host Cell Cytoskeleton and Membrane Compartments

Abstract: Human epithelial cells and the McCoy cell line were infected with Chlamydia trachomatis, serotype E. The organization of the cytoplasm was then studied with probes which stained cytoskeletal components and membrane compartments. The major actin-containing stress fibre bundles were not associated with inclusions due to the peri-basal and peri-apical location of these bundles within the host cell. The cytokeratin network was distorted by the presence of inclusions so that a common basket of these intermediate fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Inc222 and Inc850 stably interact with one another and may form a complex within the inclusion microdomains. While the functions of IncB, Inc101, and Inc222 are unknown, Inc850 may play a critical role during inclusion development by mediating microtubule-dependent trafficking of the nascent chlamydial inclusion to the perinuclear microtubule organizing center (MTOC) (Campbell et al, 1989a,b; Grieshaber et al, 2003). Inc850 was found to bind dynein light chain, DYNLT1, thus facilitating interactions between the inclusion and the host microtubule network that are required for trafficking to the MTOC (Mital et al, 2010, 2015).…”
Section: Cholesterol-rich Microdomains On Pathogen-containing Vacuolesmentioning
confidence: 99%
“…Inc222 and Inc850 stably interact with one another and may form a complex within the inclusion microdomains. While the functions of IncB, Inc101, and Inc222 are unknown, Inc850 may play a critical role during inclusion development by mediating microtubule-dependent trafficking of the nascent chlamydial inclusion to the perinuclear microtubule organizing center (MTOC) (Campbell et al, 1989a,b; Grieshaber et al, 2003). Inc850 was found to bind dynein light chain, DYNLT1, thus facilitating interactions between the inclusion and the host microtubule network that are required for trafficking to the MTOC (Mital et al, 2010, 2015).…”
Section: Cholesterol-rich Microdomains On Pathogen-containing Vacuolesmentioning
confidence: 99%
“…Instead, the inclusions provide an intracellular niche in which the pathogen can survive and complete its developmental cycle. The initial pathogen-containing endocytic vacuoles co-associate with microtubules, and dynein, and traffic to a perinuclear region, ultimately residing at the microtubule organizing center and in close proximity to the Golgi [4,5]. Here, they intercept exocytic vesicles of the biosynthetic pathway that are derived from the Golgi and continue their developmental cycle [6-9].…”
Section: Introductionmentioning
confidence: 99%
“…Mital, et al identified cholesterol-rich microdomains on the inclusion membrane that appear to serve as platforms for signaling through Src-family kinases and interaction with centrosomes and dynein (70). Once at the MTOC, the growing inclusion requires a dynamic cytoskeletal scaffold for stabilization (55, 71). The structural integrity maintained by this framework may prevent leakage of inclusion contents into the host cytosol, which might otherwise alert the host cell's innate immune system.…”
Section: Chlamydiamentioning
confidence: 99%